Pregibanje okrog telesa - Zupan Sosič, Alojzija (Slavistična revija, 2004)
Eroticism is the main topic of Vitomil Zupan's novels, a typical narrative perspective and the surce of novelistic dynamism: erotic stories, in which the narrator commonly plays a role, condense the narrative flow, while the erotic suspense renders the narrative more dynamic. In the metaphysically hollowed out world, the author recognizes the priority of art, which is, in terms of its soothing effects, similar to eroticism. The erotic vitalism goes beyond the decadent, neoromantic, existentialist, and social-realistic designs, i.e., it 'keeps' them on the fragmental level, while overlaying the historical narratives with intimate, "minor" stories.
Keywords: erotika; literarne študije; Slovene literature; slovenska književnost; slovenski pisatelji; Zupan, Vitomil, 1914-1987